Single Link Manipulator Trajectory Tracking using Nonlinear Control Algorithm - Hadi, Musadaq Ahmed; Ali, Hazem I. (Al-Nahrain Journal for Engineering Sciences, 2021)
A new robust control algorithm is proposed for a class of nonlinear systems represented by a Single Link Manipulator (SLM) system. This algorithm is based on new techniques and methods in order to obtain a controller for the SLM system. First of all, the system is simplified using Variable Transformation Technique (VTT) in order to fit the analysis procedure. Then, a new idea of designing a model reference for the multiple states (n=4) system is presented to correspond the control design. Next, the Lyapunov Stability Analysis (LSA) is used to figure out a proper controller that can compensate the stability and the performance of the SLM system. After that, the Most Valuable Player Algorithm (MVPA) is applied to find the optimal parameters of the proposed controller to accomplish the optimum performance improvement. Finally, it can be concluded that the proposed control algorithm has improved the stability and the performance of the SLM system. In addition, the simulation results show the remarkable effects of the proposed nonlinear controller on the SLM system.